Dielectric Polarization in Inverse Spinel‐Structured Mg2TiO4 Coating to Suppress Oxygen Evolution of Li‐Rich Cathode Materials. Issue 19 (2nd April 2020) - Zhang, Wei; Sun, Yonggang; Deng, Huiqiu; Ma, Jianming; Zeng, Yi; Zhu, Zhiqiang; Lv, Zhisheng; Xia, Huarong; Ge, Xiang; Cao, Shengkai; Xiao, Yao; Xi, Shibo; et al.
Abstract: High‐energy Li‐rich layered cathode materials (≈900 Wh kg −1 ) suffer from severe capacity and voltage decay during cycling, which is associated with layered‐to‐spinel phase transition and oxygen redox reaction. Current efforts mainly focus on surface modification to suppress this unwanted structural transformation. However, the true challenge probably originates from the continuous oxygen release upon charging. Here, the usage of dielectric polarization in surface coating to suppress the oxygen evolution of Li‐rich material is reported, using Mg2 TiO4 as a proof‐of‐concept material. The creation of a reverse electric field in surface layers effectively restrains the outward migration of bulk oxygen anions. Meanwhile, high oxygen‐affinity elements of Mg and Ti well stabilize the surface oxygen of Li‐rich material via enhancing the energy barrier for oxygen release reaction, verified by density functional theory simulation. Benefited from these, the modified Li‐rich electrode exhibits an impressive cyclability with a high capacity retention of ≈81% even after 700 cycles at 2 C (≈0.5 A g −1 ), far superior to ≈44% of the unmodified counterpart. In addition, Mg2 TiO4 coating greatly mitigates the voltage decay of Li‐rich material with the degradation rate reduced by ≈65%. This work proposes new insights into manipulating surface chemistry of electrode materials to control oxygen activity for high‐energy‐density rechargeable batteries. Abstract : A dielectric inverse spinel‐structured Mg2 TiO4 coating on Li‐rich cathode material significantly suppresses the continuous oxygen release, endowing batteries with remarkable cyclability and well‐inhibited voltage decay, e.g., showing a capacity retention of ≈81% and voltage degradation of only 151 mV after 700 cycles, far superior to 44% and 432 mV of the unmodified counterpart.